SANKSI PIDANA TERHADAP PENYALAHGUNAAN NARKOTIKA, GOL.1 DALAM BENTUK BUKAN TANAMAN UNTUK DIRI SENDIRI (PUT.NO.103/PID.SUS/2021/PN.JKT.SEL): Criminal Sanctions for The Abuse of Narcotics, Category 1 in The Form of Non-Plant For It Self - Bimo Ilham Wibowo; Ermania Widjajanti (AMICUS CURIAE, 2024)
According to the National Narcotics Agency, drug abuse increased from 1.80% to 1.95% in 2021-2022. This has resulted in overcrowding in prisons. The majority of inmates in correctional facilities are drug offenders, estimated at 145,413 out of 151,303 individuals. This study discusses the case of Rahmat Handoyo, also known as Doyok, who committed the crime of "Misuse of Narcotics Group I, Non-Plant-Based" and was sentenced to prison. In this case, the perpetrator should have received rehabilitation as an alternative form of punishment as stipulated by the laws and regulations. The main issue revolves around the judge's failure to impose rehabilitative measures on drug offenders. The findings of this study indicate that the judge erred in considering the decision based on applicable laws and wrongly assessed drug addicts as sick individuals, where punishment is not the appropriate answer morally and legally, taking into account the expert opinion assessment in accordance with Article 55. This research adopts a descriptive analytical approach, gathering both primary and secondary data. Primary data were obtained through interviews and were qualitatively analyzed using deductive logic, supported by secondary data from literature studies.